A review on food safety and food hygiene studies in Ghana. (January 2015) - Ababio, Patricia Foriwaa; Lovatt, Pauline
Abstract: Food safety and hygiene in Ghana was studied using desk top literature review. Food research was highly concentrated in the capital city of the country and most research focus were on commercial food operations specifically street foods and microbiological safety with limited information from institutional catering and other forms of food hazards. The media currently serves as the main source for reporting of food borne diseases. Food establishments and other sources contributing to food borne diseases included restaurants, food joints, food vendors, schools and individual homes. Limited use of prerequisites measures and food safety management systems was identified. Recommendations on regulating the General Hygiene Principles, implementation of HACCP to strengthen the food sector, regular food safety and hygiene workshops and training for food handlers that commensurate with their roles were made. Government support for SMEs and food handler's health screening were made. Highlights: Food hygiene and safety research in Ghana focussed on commercial catering in Accra. Institutional catering hygiene practices and effect on food safety was unavailable. Food allergens and physical hazards in food in the country were not identified. Food hygiene training and other PRP required legalisation in support of the Food Law. Agents in charge of food handlers monitoring and surveillance required improvement.